2020
DOI: 10.1182/bloodadvances.2019000953
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma cells induce the accumulation of activated CD94low NK cells by cell-to-cell contacts involving CD56 molecules

Abstract: Natural killer (NK) cells represent innate effector cells potentially able to play a role during the immune response against multiple myeloma (MM). To better define the distribution and the specific properties of NK cell subsets during MM disease, we analyzed their features in the bone marrow and peripheral blood of newly diagnosed MM patients. Our findings revealed that, in both compartments, NK cells were more abundant than in healthy donors. Among total MM-NK cells, a significant increase of CD94lowCD56dim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…A recent study using single-cell RNA sequencing showed enrichment of NK cell populations during MGUS, and phenotypic shifts later in MM progression that potentially point to a compromised immune system ( 66 ). Discrepancy is also observed in terms of NK cell functionality where either reduced NK cell function ( 65 ) or high NK cell function ( 59 , 67 ) are linked with advanced clinical stage, high-risk disease and reduced survival.…”
Section: Nk Cell Surveillance Of Malignant Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study using single-cell RNA sequencing showed enrichment of NK cell populations during MGUS, and phenotypic shifts later in MM progression that potentially point to a compromised immune system ( 66 ). Discrepancy is also observed in terms of NK cell functionality where either reduced NK cell function ( 65 ) or high NK cell function ( 59 , 67 ) are linked with advanced clinical stage, high-risk disease and reduced survival.…”
Section: Nk Cell Surveillance Of Malignant Cellsmentioning
confidence: 99%
“…Due to the complexity, heterogeneity, and plasticity of NK cells in cancer patients, the discrepancies are difficult to distill into a single explanation ( 67 ). One likely explanation seems to relate back to which NK cell subpopulations are being measured.…”
Section: Nk Cell Surveillance Of Malignant Cellsmentioning
confidence: 99%
See 3 more Smart Citations